Efektivitas Kemitraan Petani Kopi dengan Pondok Pesantren Ihya’us Sunnah Al-Hasany Desa Tugusari Kecamatan Bangsalsari Kabupaten Jember - Aryani, Gisca Sabrina Dwi; Soedarto, Teguh; Rizkiyah, Noor (JURNAL AGRICA, 2024)
Effectiveness is a measure that describes the extent to which goals are achieved. The effectiveness of partnerships between parties is highly dependent on the level of trust, agreement and respect for the rights and obligations of the parties during the partnership process. This study aims to identify the implementation of partnership patterns, the effectiveness of partnership patterns, and what factors influence the effectiveness of partnerships. The study was conducted at the Ihya'us Sunnah Al-Hasany Islamic Boarding School with the number of respondents taken through the purposive sampling method of 34 samples. The research method uses quantitative and qualitative description analysis, then uses the score conversion formula and the ISM (Interpretive structural modeling) method. The results of the study are that the partnership patterns applied by coffee farmers with the Ihya'us Sunnah Al-Hasany Islamic Boarding School are general trade partnership patterns and Agribusiness Operational Cooperation (KOA) partnership patterns, Partnership effectiveness based on partnership performance, coffee farmer participation, and coffee farming is very effective, while the effectiveness of the partnership based on mentoring from the Ihya'us Sunnah Al-Hasany Islamic Boarding School is effective. The obstacles faced in the partnership between coffee farmers and the Ihya'us Sunnah Al-Hasany Islamic Boarding School with the criteria of structured obstacles, namely middlemen as the main priority.